Improving production workflow processes in printing industry using simulation - Ong, Mei Hwei (2014)
In this study, it discusses about improving production workflow process in printing industry using simulation. The scope of this study is focusing on the production workflow of printing soft cover books. The time frame covered is one year it is in the year of 2013. This study is conducted by using the ARENA simulation software to simulate the modeled process in the simulation software. It is a quantitative study in which the performance is measured by the cycle time for the whole system of book printing.